Analisis Strategi Marketing Mix Dalam Perspektif Syariah Untuk Meningkatkan Penjualan Jasa Dan Produk - Rizka Salsabila; Chuzaimah Batubara (LPPM Universitas Labuhanbatu, 2025)
The development of modern business requires the use of marketing methods that can help the company grow. Because marketing activities are company activities that are directly related to the wider community (consumers), the success of this activity will greatly affect the development or failure of business activities. One of the fundamental ideas in contemporary marketing is the marketing mix. The marketing mix is a group of tactical marketing tools that can be controlled and combined by the company to obtain the desired response in the target market. Islamic marketing as a concept is actually not much different from the understanding of marketing in the modern world, which is an art and science that leads to the process of generating, delivering, and conveying value to consumers and maintaining sustainable relationships with stakeholders. To further establish a quality plan that can be relied upon to advance the marketing sector in particular and the economy in general, the Marketing Mix strategy will undoubtedly be very interesting if evaluated from a sharia perspective. The approach used in this research is a literature review, which takes information from books and journal articles.